2022
DOI: 10.3390/w14233941
|View full text |Cite
|
Sign up to set email alerts
|

Develop a Smart Microclimate Control System for Greenhouses through System Dynamics and Machine Learning Techniques

Abstract: Agriculture is extremely vulnerable to climate change. Greenhouse farming is recognized as a promising measure against climate change. Nevertheless, greenhouse farming frequently encounters environmental adversity, especially greenhouses built to protect against typhoons. Short-term microclimate prediction is challenging because meteorological variables are strongly interconnected and change rapidly. Therefore, this study proposes a water-centric smart microclimate-control system (SMCS) that fuses system dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Previous research revealed that, when compared to the traditional greenhouse spraying system, the Smart Microclimate Control System for Greenhouses could save 66.8% of the water and energy (electricity) used for early spraying throughout the cultivation period. This finding demonstrates how the SMCS will strengthen agricultural resilience to hydro-climate uncertainty and encourage the conservation of resources (Chen et al, 2022). Using a Supervisory Control and Data Acquisition (SCADA) system and a Programmable Logic Controller (PLC), a monitoring system was created to precisely control and predict the conditions of a greenhouse (Ding et al, 2018).…”
Section: )mentioning
confidence: 96%
“…Previous research revealed that, when compared to the traditional greenhouse spraying system, the Smart Microclimate Control System for Greenhouses could save 66.8% of the water and energy (electricity) used for early spraying throughout the cultivation period. This finding demonstrates how the SMCS will strengthen agricultural resilience to hydro-climate uncertainty and encourage the conservation of resources (Chen et al, 2022). Using a Supervisory Control and Data Acquisition (SCADA) system and a Programmable Logic Controller (PLC), a monitoring system was created to precisely control and predict the conditions of a greenhouse (Ding et al, 2018).…”
Section: )mentioning
confidence: 96%
“…The prediction of a short-term microclimate is a challenging task due to the rapid changes and strong interconnections among meteorological variables. To address this issue, Chen et al introduced a water-centric smart microclimate control system (SMCS) that incorporates system dynamics and machine learning techniques, which can regulate the micro-environment within a greenhouse canopy to induce environmental cooling while improving resource-use efficiency [25]. The proposed SMCS demonstrates the practicality of machine-learning-enabled greenhouse automation that enhances crop productivity and resource-use efficiency, thereby contributing to the mitigation of carbon emissions and a sustainable water-energy-food nexus.…”
Section: Smart Microclimate Control System Using Aimentioning
confidence: 99%
“…ANNs are utilized in hydrological studies, including urban flood forecasting [19,20], groundwater level prediction [21], rainfall-runoff prediction [22], water quality modeling [23,24], and microclimate prediction [25]. ANNs are becoming increasingly popular in predicting greenhouse microclimates as they can quickly and accurately analyze large amounts of data [26,27].…”
Section: Related Workmentioning
confidence: 99%